Transparency in Lobbying as Perceived by Organisational Representatives in the Czech Republic - Lucie Vnoučková; Milan Žák (Review of Economic Perspectives, 2017)
This paper focuses on transparency in lobbying as perceived by in sample organisations in the Czech Republic. The paper's aim is to study how lobbying and its impact on decision-making practices are perceived by organisational representatives and to empirically assess the perceived transparency of lobbying with a view to the potential introduction of lobbying regulations and their role in Czech democracy. Data for the study was gathered from a sample of business institutions in the Czech Republic. In total, 73 organisations/institutions took part in the survey. One respondent was questioned per organisation/institution. 90 % of respondents perceive that transparent and regulated lobbying has a positive impact on democracy. Moreover, according to the respondents, lobbying facilitates more competent decision-making among politicians, brings more information into the decision-making process and makes the process more efficient. There has been a significant shift in the perception of lobbying over the past ten years in the Czech Republic. Regulations aimed at legitimizing lobbying are seen as having a positive impact on democracy.
Keywords: 330; Lobbying; transparency; democracy; stakeholders; regulation; perception